Improving The Digital Literacy of Science Teachers Through A STEM Approach Based on Artificial Intelligence to Realize Deep Learning - Widiyatmoko, Arif; Fibriana, Fidia; Aji, Septiko; Wulandari, Tiara Dwi; Nursulistari, Siti; Mayanti, Alfiana Nur Rosita (Universitas Negeri Semarang, 2025)
Digital literacy is one of the important competencies for science teachers as educators in learning in the 21st century. Unfortunately, not every teacher has good mastery so training is needed to improve digital literacy. The purpose of this service is to improve the digital literacy of junior high school science teachers in Semarang City through AI-based STEM learning activities in deep learning science learning. The training method uses facilitation-based action learning which begins with the presentation of material by the speaker, science learning practices by integrating STEM, AI, deep learning, questions and answers and closing. The results of the study showed that there was an increase in the digital literacy of science teachers in Semarang City after attending the training. The presentation of materials by resource persons and case study-based practical activities on science learning with an AI-assisted STEM approach and applying the principles of deep learning mindful learning, meaningful learning, and joyful learning are able to improve teachers' mastery of digital literacy. Participants also gave positive responses to the feasibility of the training materials and presentation. This means that the implementation of training to improve the digital literacy of science teachers with AI-based STEM and deep learning has been carried out very well.